Unravelling International Students' Preferences in Embracing Malaysian Cuisine: A Pilot Study (Journal of Science, Technology and Innovation Policy, 2024)
This pilot study aims to investigate the preferences of international students in embracing Malaysian cuisine during their tenure at local university. Students frequently experience difficulties in their social and academic environments. No study has been explored on the relationship between students’ views and perceptions of Malaysian food. The objective of this study is to precede further studies on key factors that influence international students' preferences for Malaysian cuisine that may perhaps provide insights for universities and local food establishments to promote more of Malaysian cuisine internationally. The pilot study was conducted at Universiti Teknologi Malaysia, Kuala Lumpur branch, which consist of a significant number of undergraduate and postgraduate international students. Kuala Lumpur has many options for type of restaurants and varieties of local cuisine. The research instrument used in this study is a self-administered questionnaire, that was validated and distributed to only international students. The study employed a quantitative method approach to understand the factors influencing the food choices of international students, towards Malaysian cuisine. The questionnaire developed includes demographic information, followed by the Theory of Planned Behaviour (TPB) sections, (i) attitude, (ii) subjective norms and (iii) perceived behavioural control. The findings of this pilot do prove that attitudes, social norm and perceived behavioural control had a significant positive effect on intention to consume Malaysian food with attitudes playing the main factor. The quality, taste and cultural background of the food product are the drivers that led them to consume local cuisine. This study has provided valuable insights for further research and the development of strategies to cater to the culinary preferences of international students in UTM Kuala Lumpur especially. The findings thus far could provide insights for local food establishments to enhance the promotion of Malaysian cuisine to international students, to potentially increase the demand for local foods and boost the industry's revenue.
Keywords: International students, intention, Malaysia, food, culture, taste